2015
DOI: 10.1007/s10689-015-9817-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to clinical utilization of hereditary cancer gene panel testing: perspectives from the front lines

Abstract: Next generation sequencing (NGS) technology is rapidly being implemented into clinical practice. Qualitative research was performed to gain an improved understanding of the landscape surrounding the use of NGS in cancer genetics. A focus group was conducted at the Wisconsin Cancer Risk Programs Network biannual meeting. Free flowing discussion with occasional open-ended questions provided insights into the use of NGS. 19 genetic counselors and medical professionals participated. Three major themes were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…However, the use of comprehensive multigene panel testing has become increasingly prevalent and has helped to identify additional patients with BRCA1/2 mutations as well as patients with mutations in other genes associated with an increased risk. Although a multigene testing approach provides advantages in terms of comprehensive assessment, cost and turnaround time, the goals of practical clinical utility and ease of interpretation should always be kept in mind (101,102), in addition to the care that should be taken to ensure extensive and in-depth clinical and analytical validation (103).…”
Section: Genetic Testingmentioning
confidence: 99%
“…However, the use of comprehensive multigene panel testing has become increasingly prevalent and has helped to identify additional patients with BRCA1/2 mutations as well as patients with mutations in other genes associated with an increased risk. Although a multigene testing approach provides advantages in terms of comprehensive assessment, cost and turnaround time, the goals of practical clinical utility and ease of interpretation should always be kept in mind (101,102), in addition to the care that should be taken to ensure extensive and in-depth clinical and analytical validation (103).…”
Section: Genetic Testingmentioning
confidence: 99%
“…Studies using paired tumor-normal data found that tumor sequencing can detect germline pathogenic variants in 4–12% of patients 10–12. Because determining which tumor-detected pathogenic variants deserve germline analysis is challenging, ESMO convened its subgroup to address germline management of tumor-detected variants 6 9 13. The subgroup recommended germline follow-up analysis for 27 genes with high or standard actionability that had two or more mutations of true germline origin detected across relevant tumor types and a >10% germline conversion rate (number of pathogenic variants of true germline origin × 100/total number of tumor detected pathogenic variants).…”
Section: Discussionmentioning
confidence: 99%
“…Die NGS-Technologie kann gleichzeitig Informationen über verschiedene genetische Varianten mit unterschiedlichen funktionellen und klinischen Konsequenzen produzieren. Die Herausforderungen der humangenetischen Beratung (Keimbahndiagnostik) in der NGS-Testung liegen in der großen Anzahl untersuchter Gene, im Auftreten von unerwarteten Ergebnissen, in der Interpretation der Phänotyp-Genotyp-Zusammenhänge aller untersuchten Gene, im Fehlen von spezifischen, auf NGS ausgerichteten Guidelines, im Fehlen von spezifischen Daten für entsprechende Richtlinien und in der Standardisierung von NGS sowie in der Interpretation von sogenannten "Varianten unklarer klinischer Signifikanz" (VUS) [29][30][31]. Fallbeispiele aus der Praxis mit Einführung von WES oder WGS zeigen, dass der NGS-basierte Beratungsprozess von Keimbahnmutationen zeitlich deutlich mehr in Anspruch nimmt und thematisch umfassender und aufwendiger ist [32].…”
Section: Humangenetische Beratung Von Keimbahnmutationen In Der Ngs-äraunclassified